“Human Beings Is What Women Want to Become, and to Partake of the Garland of Work and Victory.” Visions of Emancipation, Community Spirit, and Social Reform in the First German Women's Movement - Schötz, Susanne (Frontiers in Sociology, 2019)
My reflections draw attention to the General German Women’s Association (German: Allgemeiner Deutscher Frauenverein – ADF), which was founded on 18th October 1865 under the chairwomanship of writer, journalist and publicist Louise Otto-Peters (1819-1865). This event marks the beginning of the organized women’s movement in Germany. I will pay special attention to Louise Otto-Peters, who not only initiated the ADF and chaired it for many years, she was also its most important theoretical thinker and, crucially, developed specific policies for women. This happened at a time when women were largely excluded by law from political participation. They did not have the right to vote until 1918 and were therefore unable to play any role in city and state parliaments, or in the Reichstag, either. Until 1908, they were not even allowed to be members of political parties or associations with a political orientation. The first part of this article sets out to depict Louise Otto-Peter’s views and visions based mainly on her writings “Das Recht der Frauen auf Erwerb. Blicke auf das Frauenleben der Gegenwart” (The Right of Women to Gainful Employment. Views on Contemporary Women’s Lives) from 1866, and “Frauenleben im Deutschen Reich. Erinnerungen aus der Vergangenheit mit Hinweis auf Gegenwart und Zukunft” (Women’s Lives in the German Reich. Memories from the Past with Reference to the Present and Future) from 1876. The second part attempts an appraisal of her ideas against the backdrop of the existing gender order and the dominant gender thinking. Part three is interested in the legitimization of her visions and, to this end, examines important – but by no means all – discernible lines of argumentation and interpretations.